Comparative evaluation of efficacy of autogenous platelet rich plasma versus visco supplementation in treatment of early osteoarthritis of knee - Shantanu, Kumar; Singh, Shailendra; Navadaya, Mahesh Kumar; Patel, Brijmohan (International Journal of Research in Orthopaedics, 2019)
Background: Osteoarthritis is a very common chronic degenerative disease most commonly affecting the knee joints. In present study we compared the efficacy of autogenous platelet rich plasma (PRP) versus visco supplementation in treatment of early osteoarthritis of knees. Methods: 30 patients (56 knees) were registered and divided into two groups. Out of which PRP in 28 knees and visco supplementation in 28 knees injected during. Visual analogue scale (VAS) and Western Ontario and McMaster Universities Arthritis Index (WOMAC) scores were measured. These scores were measured at first visit, 6 weeks, 12 weeks and at 24 weeks. Results: All registered patients were randomized in two groups. Group I (total 16 patients and 28 knees) for intraarticular PRP injection and group II (total 14 patients and 28 knees) for intraarticular viscosupplement injection. Out of 28 knees of group I; 12 (42.85%) knees belonged to grade II and 16 (57.15%) of grade III. Out of 28 knees of group II; 15 (53.57%) knees of grade II and 13 (46.45%) of grade III. None of the knees belonged to grade I and grade 0. There was significant difference in outcome of two treatment groups (p<0.05) at 24 weeks. Conclusions: Treatment with PRP showed a significantly better clinical outcome compared with viscosupplemention at 24 weeks follow up. Although patients achieved lower WOMAC and VAS scores in PRP group at 6 and 12 weeks follow up that was statistically insignificant. We conclude that long term results of PRP are better than viscosupplementation.